2010
DOI: 10.4317/jced.2.e26
|View full text |Cite
|
Sign up to set email alerts
|

Successful closure of the root apex in non-vital permanent incisors with wide open apices using single calcium hydroxide (caoh) dressing - report of 2 cases

Abstract: Endodontic management of immature non vital permanent teeth in young pediatric patients is a great challenge to dentists. The walls of the root canals are frequently divergent and open apexes make debridement and obturation difficult. Thus closure of root apex is very essential for success of the endodontic treatment. Although different materials are used for the apexification procedure, calcium hydroxide is the material of choice for apical barrier formation and healing. There are different opinions regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
(11 reference statements)
0
7
0
2
Order By: Relevance
“…Because of its enhanced success rate, easy availability for clinician and affordability for patients it gained widest acceptance in literature. [6] Sheehy and Roberts showed that the use of calcium hydroxide for apical barrier formation was successful in 74-100% of cases and average time for barrier formation ranged from 5 to 20 months. [7] The artificial apical barrier technique is a contemporary approach for managing open apices cases.…”
Section: Discussionmentioning
confidence: 98%
“…Because of its enhanced success rate, easy availability for clinician and affordability for patients it gained widest acceptance in literature. [6] Sheehy and Roberts showed that the use of calcium hydroxide for apical barrier formation was successful in 74-100% of cases and average time for barrier formation ranged from 5 to 20 months. [7] The artificial apical barrier technique is a contemporary approach for managing open apices cases.…”
Section: Discussionmentioning
confidence: 98%
“…The use of Ca(OH) 2 in apical barrier formation has shown promising results. Because of its enhanced success rate, easy availability for the clinician, and affordability for patients, it has gained the widest acceptance in the literature (17).…”
Section: Discussionmentioning
confidence: 99%
“…The use of Ca(OH) 2 in apical barrier formation has shown promising results. Because of its enhanced success rate, easy availability for the clinician, and affordability for patients, it has gained the widest acceptance in the literature (17). Sheehy and Roberts reported that the use of calcium hydroxide for apical barrier formation was successful in 74 -100% of cases, and the average time for apical barrier formation ranged from 5 to 20 months (18).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium hydroxide was introduced to the field of endodontics by Herman in 1930 as a pulp capping agent. Because of its enhanced success rate, easy availability for clinician and affordability for patients, Ca(OH) 2 gained widest acceptance in literature [15].…”
Section: Discussionmentioning
confidence: 99%